IMPROVING CHILDREN'S SOCIAL DEVELOPMENT THROUGH PICENG TRADITIONAL GAMES FOR CHILDREN AGED 5-6 YEARS (International Conference on Social and Islamic Studies, 2022)
Stimulation in aspects of early childhood development is very important, especially in aspects of social development. There are various ways to stimulate children's social development to develop optimally, one of which is using the traditional Piceng game media. The research objective was to determine the increase in children's social development through traditional games in children aged 5-6 years. The research method used is quantitative research with experimental types, a sample of 6 children aged 5-6 years, the sampling technique uses purposive sampling by determining certain limits or criteria, the research instrument uses rating scale observation sheets and data analysis techniques use the Wilcoxon test and program Output Spss. The stages of the research are observation before giving treatment, giving treatment, observing after giving treatment and conducting data analysis. Based on the results of the study, before and after using the traditional Piceng game, the pretest average score was 34.33 40 and the post test was 51.16 with a hypothetical mean value of 40. It can be concluded that the posttest value experienced a significant increase and exceeded the hypothetical mean value so that it can be concluded that there is increasing social development through traditional piceng games. The implications of this research can be used to develop research related to early childhood social development, as well as preserving and using traditional games as a medium in stimulating early childhood development.